ANALISIS PENERAPAN FUNGSI DAN MANAJEMEN DALAM MENINGKATKAN KINERJA LEMBAGA PENDIDIKAN USIA DINI (STUDI KASUS PADA PIAUD UIN RADEN FATAH) - Fahmi, Fahmi; Bunga Mentari, Eca; Marsyanda, Marsyanda; Rosyada, Amrina; AfifathurRohmah, Hanif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of management functions (planning, organizing, actuating, and controlling) in improving the performance of early childhood education institutions in the Early Childhood Islamic Education Study Program (PIAUD) at UIN Raden Fatah. A qualitative approach with a case study method was employed through data collection techniques including observation, interviews, and documentation involving program leaders, lecturers, and educational staff. The results indicate that the implementation of management functions has been carried out systematically: planning includes the formulation of vision and mission as well as structured work programs; organizing is conducted through a clear division of tasks; the implementation of academic and non-academic activities is relatively in accordance with the plan despite some technical constraints; and controlling is conducted through periodic evaluations. This effective implementation contributes to improving learning quality, educators’ professionalism, and institutional management effectiveness. Therefore, continuous optimization of management functions is the key to improving the quality of early childhood education.